The Long Path of Human Placenta, and Its Derivatives, in Regenerative Medicine - Silini, Antonietta R.; Cargnoni, Anna; Magatti, Marta; Pianta, Stefano; Parolini, Ornella (Frontiers in Bioengineering and Biotechnology, 2015)
In the 1800’s, a baby born with a caul, a remnant of the amniotic sack or fetal membranes, was thought to be lucky, special, or protected. Over time, fetal membranes lost their legendary power and were soon considered nothing more than biological waste after birth. However, placenta tissues have reclaimed their potential and since the early 1900’s an increasing body of evidence has shown that these tissues have clinical benefits in a wide range of wound repair and surgical applications. Nowadays, there is a concerted effort to understand the mechanisms underlying the beneficial effects of placental tissues, and, more recently, cells derived thereof. This review will summarize the historical and current clinical applications of human placental tissues, and cells isolated from these tissues, and discuss some mechanisms thought to be responsible for the therapeutic effects observed after tissue and/or cell transplantation.